Enzymatic pretreatment of wastewater for enhanced biogas production - Alam, Md. Zahangir; Sabri, Norshakila; Jafar, Abu; Tajul Islam, M. S. (2015)

(untitled)
A renewable energy has been developed as to provide one of the solutions to the energy issues. Based on the origin of renewable energy and resources, many countries have researched and developed the renewable energies such as solar, wind, geothermal, nuclear and biogas. Among them, biogas has been evaluated as one of the most energy-efficient and environmentally beneficial technologies for bioenergy production. Energy from biogas not only compensates the imported fuel but also reduce the pollution associated with converting biowaste or even biomass to the valuable biogas. The most challenging step of enhanced biogas production by anaerobic digestion is the HYDROLYSIS among the three steps. This invention develops an effective enzymatic hydrolysis (hydrolytic enzymes: lipase and cellulase) of Indah Water Konsortium (IWK) sludge/palm oil mill effluent (POME) for enhanced biogas production. Several treatment processes such as pretreatment (hydrolysis), acidogenesis, acetogenesis and methanogenesis are developed for bioconversion of wastewater into biogas.